PELATIHAN ENGLISH READING SKILL FOR CONSTRUCTION AND PROPERTY BUSINESS BAGI KELAS X JURUSAN BISNIS KONSTRUKSI DAN PROPERTI DI SEKOLAH MENENGAH KEJURUAN NEGERI JAWA TENGAH, SEMARANG - Cut Aja Puan Ellisafny; Ratna Asmarani; Hadiyanto Hadiyanto (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2020)
In the competitive world of construction and property business, the skill to speak and to read a foreign language is important in this modern era. Through these articles made based on community service activities specifically aimed at students of Central Java Vocational School, Semarang. Dedication in the form of training in English Reading Skills for construction and property business. The aim is to train students of SMK Central Java, Semarang in reading and understanding the context of sentences construction and property business in English. The training is carried out by equipping students with material or theory followed by practice in understanding English texts. In this training, students can properly and correctly recognize the context of English reading. It is expected that later students in the contruction and property business majors at SMK Central Java, Semarang can compete in the conctruction and property business world by mastering the language of international communication namely English. Keyword: English learning, Learning Reading skill and Comprehension, construction and property business.